2017
DOI: 10.18632/oncotarget.15716
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 antibody as a potential diagnostic and prognostic biomarker in patients with dermatomyositis

Abstract: The presence of anti-MDA5 antibodies in serum represents an important biomarker in the diagnosis and prediction of prognosis for patients with idiopathic inflammatory myopathies (IIMs). Due to conflicting results that have been reported regarding the detection of anti-MDA5 antibodies, the goal of this study was to assess a potential association between the presence of anti-MDA5 antibodies and dermatomyositis/polymyositis (DM/PM), as well as the diagnostic and prognostic values of anti-MDA5 antibodies for DM/PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Our study did not show any difference in survival prognosis between CADM and classical DM. The data suggest that serological anti-MDA5 Ab is more closely associated with acute progressive ILD than CADM as a clinical phenotype, as previous studies have shown that patients with classical DM anti-MDA5 Ab present with rapidly progressive ILD as do patients with seropositive CADM [ 22 24 ]. Serum ferritin level has been shown to be a biomarker for the activity of ILD in patients with PM/DM [ 25 ].…”
Section: Discussionmentioning
confidence: 60%
“…Our study did not show any difference in survival prognosis between CADM and classical DM. The data suggest that serological anti-MDA5 Ab is more closely associated with acute progressive ILD than CADM as a clinical phenotype, as previous studies have shown that patients with classical DM anti-MDA5 Ab present with rapidly progressive ILD as do patients with seropositive CADM [ 22 24 ]. Serum ferritin level has been shown to be a biomarker for the activity of ILD in patients with PM/DM [ 25 ].…”
Section: Discussionmentioning
confidence: 60%
“…Narang et al [4] reported that cutaneous ulcerations were present in 28% of 152 patients with DM and that the ulceration had potential associations with autoantibody status. The anti-melanoma differentiation-associated gene 5 antibody is known to be associated with skin ulceration in DM [5]. Cutaneous ulcerations commonly occur over Gottron papules or in areas with the Gottron sign, and often affect the skin over the extensor joint surfaces, although they could be found anywhere [6].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anti-MDA5 antibodies has been strongly associated with RP-ILD in DM, especially in the CADM subtype [12]. A recent meta-analysis has shown they have a good sensitivity (83%) and specificity (86%) for identifying the risk of RP-ILD in this subset of patients [13]. Thus, anti-MDA5 antibodies have been proposed as a useful surrogate marker of disease activity [14][15][16].…”
Section: Discussionmentioning
confidence: 99%